We how to increase performance and profits through full engagement - Karsan, Rudy (Tantor Media, 2011)
Using research and academic insights translated into actionable steps, this guide provides both managers and individual employees with a road map to full engagement, increased productivity, and overall satisfaction in their jobs.
Keywords: Employee motivation; Organizational effectiveness; Personnel; Motivation; Efficacité organisationnelle; BUSINESS & ECONOMICS; Workplace Culture; BUSINESS & ECONOMICS; Human Resources & Personnel Management; Downloadable audio books; Audiobooks; Electronic audio books; Livres audio